Natural and anthropogenic influences on the population structure of white‐tailed eagles in the Carpathian Basin and central Europe - Edina Nemesházi; Szilvia Kövér; Frank E. Zachos; Zoltán Horváth; Gábor Tihanyi; Attila Mórocz; Tibor Mikuska; István Hám; Ivan Literák; Suvi Ponnikas; Tadeusz Mizera; Krisztián Szabó (Journal of Avian Biology, 2016)
European populations of the white‐tailed eagle Haliaeetus albicilla suffered a drastic decline during the 20th century. In many countries, only a few dozen breeding pairs survived or the species disappeared completely. By today, the populations have recovered, naturally or through restocking (e.g. in Scotland or the Czech Republic). In the Carpathian Basin, which is now a stronghold in southern Europe for the species in the southern part of the distribution range with more than 500 breeding pairs, only about 50 pairs survived the bottleneck. This region provides important wintering places for individuals arriving from different regions of Eurasia. In the present study, we investigated 249 DNA samples from several European countries, using 11 microsatellites and mitochondrial control region sequences (499 bp), to answer two main questions: 1) did the Carpathian Basin population recover through local population expansion or is there a significant gene flow from more distant populations as well? 2) Does the Czech population show signs in its genetic structure of the restocking with birds of unknown origin? Our microsatellite data yielded three genetically separate lineages within Europe: northern, central and southern, the latter being present exclusively in the Carpathian Basin. Sequencing of mitochondrial DNA revealed that there is one haplotype (B12) which is not only exclusive to the Carpathian Basin but it is frequent in this population. Our results suggest that in accordance with the presumably philopatric behaviour of the species, recovery of the Carpathian Basin population was mainly local, but some of the wintering birds coming from the northern and central populations contributed to its genetic composition as well. We detected considerably higher proportions of northern birds within the Czech Republic compared to the neighbouring areas, making it likely that parents of the reintroduced birds came from northern populations.